ANALYSIS OF CLOTHING MANUFACTURERS OF HALAL PRODUCTS IN THE CLOTHING INDUSTRY, (STUDY ON CLOTHING PRODUCERS IN THE CITY OF MATARAM) - Syahrul Hanafi (Universitas Islam Negeri Mataram, 2019)
Halal clothing is one part of the halal industry that is targeted to be developed in Indonesia, given the considerable potential needed such as other halal industrial sectors more than Islamic finance, halal food, halal cosmetics, and halal tourism. Unlike the Islamic finance and halal food industries, knowledge of halal clothing in the community is still very low. Expect limited halal-haram limited only to food and financial problems. This is a challenge in the development of the halal clothing industry in Indonesia.The objectives of this study include 1) To analyze the clothing manufacturer's knowledge of the concept of halal clothing based on the supply chain; 2) To analyze the process of producing clothes and analyze the concept of halal clothing; 3) The views of clothing manufacturers on the concept of halal clothing. The research method in this research is descriptive qualitative. The technique of collecting data using interviews and observations, while to restore the validity of the data using triangulation techniques. The research subjects in this study were the clothing manufacturers in the city of Mataram.1) Knowledge of clothing producers about the concept of halal clothing 2) the production process and SOP that are carried out by producers are still very simple, this changes the producers do not have the readiness to carry out the production process based on the concept of halal clothing based on the supply chain; 3) According to the producers voluntary to meet the indicators on halal clothing based on the supply chain. According to the producers, the first aspects that are difficult to agree to include: 1) procurement of halal raw materials; 2) halal warehousing; and 3) SOP for halal clothing.